Analysis of PT Hakaaston's Business Transformation - Ranggaditya Wisnu P; Zuliani Dalimunthe (Green Publisher Indonesia, 2025)
This study analyzes the role of leadership and organizational culture in supporting the business transformation of PT Hakaaston, which shifted from a construction-related manufacturing company to a toll road operations and maintenance service provider. Using a qualitative case study approach, data were collected through in-depth interviews with 13 management-level respondents and financial report analysis covering the 2018–2024 period. The findings reveal that agile and transformational leadership played a crucial role in shaping strategic vision, fostering two-way communication, and empowering employees through coaching and training initiatives. Organizational culture also supported the transformation through the internalization of AKHLAK core values and the development of an adaptive and agile culture that enabled the company to respond flexibly to environmental changes. Although revenue declined due to the change in business focus, the transformation led to improved operational efficiency and financial structure. These results affirm that the integration of visionary leadership and a supportive organizational culture is fundamental to successful strategic transformation, offering practical insights for state-owned enterprises and other organizations navigating long-term structural change.